2018
DOI: 10.1002/jcp.27048
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Effects of FOSL1 silencing on osteosarcoma cell proliferation, invasion and migration through the ERK/AP‐1 signaling pathway

Abstract: Osteosarcoma (OS), as the most frequent primary malignancy of bone, is characterized by the presence of malignant mesenchymal cells. In the current study, our aim was to explore the possible effects Fos-like antigen-1 (FOSL1) had on the silencing regarding OS cell proliferation, invasion, and migration through the activation of the extracellular-signal-regulated kinase (ERK)/activator protein-1 (AP-1) signaling pathway. After the collection of OS on top of already having the adjacent normal tissue samples, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…AP-1 transcription factor is a dimeric transcription factor encompassing a group of structurally and functionally related members of c-Jun, c-Fos, ATF, and MAF protein families [ 42 44 ] and it can therefore form many different combinations of heterodimers and homodimers, and this combination determines the genes that are regulated by AP-1 [ 45 ]. AP-1 can regulate a wide range of biological processes including proliferation, differentiation, apoptosis, survival, migration, invasion, and transformation [ 42 , 44 , 46 50 ]. The activation of the AP-1 is regulated at two major levels: extracellular stimuli modulate both the abundance and the activity of AP-1 proteins.…”
Section: Discussionmentioning
confidence: 99%
“…AP-1 transcription factor is a dimeric transcription factor encompassing a group of structurally and functionally related members of c-Jun, c-Fos, ATF, and MAF protein families [ 42 44 ] and it can therefore form many different combinations of heterodimers and homodimers, and this combination determines the genes that are regulated by AP-1 [ 45 ]. AP-1 can regulate a wide range of biological processes including proliferation, differentiation, apoptosis, survival, migration, invasion, and transformation [ 42 , 44 , 46 50 ]. The activation of the AP-1 is regulated at two major levels: extracellular stimuli modulate both the abundance and the activity of AP-1 proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, regarding the 18 network node genes (Figure 5A) that were finally identified in this study, many groups have shown that they play a significant role in the regulation and linkage of related pathways in trauma, skin wound healing, inflammatory processes and inflammation-related diseases, tumor progression, and other inflammation-related biological repair processes (Han et al, 2019;Kumar et al, 2020;Wang et al, 2020) (Table 2). Studies showed that among Fos proteins, including Fosl1, significantly bind to the promoter regions of multiple genes and differentially regulate the expression level of related genes during the processes of tissue and cell damage, repair and differentiation (Reddy and Mossman, 2002).…”
Section: Discussionmentioning
confidence: 82%
“…Here, SFPQ levels were enriched at the FOSL1 promoter and induced its transcriptional activity in NPC. FOSL1 belongs to the AP-1 transcription factor family and can stimulate tumor cell proliferation and metastasis [ 35 , 36 ]. In this study, FOSL1 promoted NPC cell proliferation, migration and invasion, and ectopic expression of FOSL1 reversed the inhibitory effect of LINC01503 knockdown in NPC.…”
Section: Discussionmentioning
confidence: 99%